Anterior cruciate ligament injuries: treatment and rehabilitation - Cross, M. J. (Encyclopedia of Sports Medicine and Science, 1998)
Of specifically ligamentous injuries to the knee, rupture of the Anterior Cruciate Ligament (ACL) has been the commonest, and has the greatest potential to cause both short term and long term disability. In this connection the article deals with: - Functional Anatomy, - Rationale for Treatment, - Causes of ACL Rupture, - History, - Examination, - Management of the Ruptured ACL.